2011
DOI: 10.1539/joh.10-0073-oa
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Impaired Fasting Glucose and Noise‐induced Hearing Loss

Abstract: The Association between Impaired FastingGlucose and Noise-induced Hearing Loss: Tae-Won Jang, et al. Department of Occupational and Environmental Medicine, Hangang Sacred Heart Hospital, Hallym University College of Medicine, Korea-Objectives: This study was performed to determine whether there is an association between impaired fasting glucose and noise-induced hearing loss. Methods: The study subjects were workers in one automobile manufacturing company. The data were obtained from results of health examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…In a previous study of workers in an automobile manufacturing company, those with IFG had greater incremental change of hearing thresholds than those with normal fasting glucose levels during a 4‐year follow‐up period, suggesting that workers with IFG were more susceptible to noise‐induced hearing loss. In that study, only the 4000 Hz threshold was measured in the workers exposed to occupational noise . A cross‐sectional study using a veteran cohort reported that pre‐diabetes, which was defined as subjects with < 38.8 mmol/mol, showed a tendency to have higher pure‐tone average of thresholds at low to high‐frequency compared to subjects with normal glucose levels, however, no difference remained after adjustment for age.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study of workers in an automobile manufacturing company, those with IFG had greater incremental change of hearing thresholds than those with normal fasting glucose levels during a 4‐year follow‐up period, suggesting that workers with IFG were more susceptible to noise‐induced hearing loss. In that study, only the 4000 Hz threshold was measured in the workers exposed to occupational noise . A cross‐sectional study using a veteran cohort reported that pre‐diabetes, which was defined as subjects with < 38.8 mmol/mol, showed a tendency to have higher pure‐tone average of thresholds at low to high‐frequency compared to subjects with normal glucose levels, however, no difference remained after adjustment for age.…”
Section: Discussionmentioning
confidence: 99%
“…Another survey observed significant interactions between firearm noise exposure and hearing loss in diabetic patients at 3 kHz (36). Automobile company workers with high fasting blood glucose levels showed significantly higher hearing thresholds at 4 kHz than workers with normal fasting glucose levels (14). These studies and ours suggest that patients with diabetes are potentially more susceptible to noise-induced hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, using a large population-based dataset, Bainbridge, Hoffman, and Cowie concluded that diabetes is an independent risk factor for hearing loss (12). In addition, interactions between noise exposure and diabetes were reported (13,14). …”
mentioning
confidence: 99%
“…However, studies exploring the direct association between atherogenic risk factors and hearing loss show inconsistent findings: dyslipidemia in terms of elevated levels of total cholesterol, low-density lipoprotein (LDL), triglycerides (TG) and low levels of high-density lipoprotein (HDL) have shown mainly adverse effects on hearing ability [Gates et al, 1993;Suzuki et al, 2000;Shargorodsky et al, 2010] but a gainful effect of high total cholesterol level has also been reported [Jones and Davis, 2000]. A relation between hearing ability and diabetes-related measures has been reported in several studies [Austin et al, 2009;Jang et al, 2011;Akinpelu et al, 2014], which is also the case for smoking [Fransen et al, 2008;Shargorodsky et al, 2010] and high BMI [Fransen et al, 2008;Lalwani et al, 2013]. Other studies, however, have shown conflicting results for these factors [Gates et al, 1993;Shargorodsky et al, 2010].…”
Section: Introductionmentioning
confidence: 99%